2011
DOI: 10.1111/j.1439-0469.2011.00638.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure of the common impala (Aepyceros melampus melampus) in South Africa: phylogeography and implications for conservation

Abstract: We analysed 131 common impala (Aepyceros melampus melampus) samples from two provinces in South Africa (Limpopo and KwaZulu-Natal) that are separated by the Drakensberg Mountain Range using sequences of the mitochondrial control region and seven polymorphic nuclear microsatellite loci. In line with earlier studies on bovid species, we found very high values of genetic diversity, particularly at the mtDNA locus with an overall nucleotide diversity of 3.6% and an overall haplotype diversity of 0.98. All statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…This same pattern, which includes a northern coastal population with an otherwise inland group, has also been described in impala ( Aepyceros melampus ) by Schwab et al (2012) and other South African mammals (Lawes et al, 2007). Cooke (1962), Van Zinderen Bakker (1978) and Scott (2002) suggested that evergreen forest may have stretched from the northern region (NE1/NE2) into KwaZulu-Natal (NC1) before and after the last glacial maxima, 16,000–18,000 years before present.…”
Section: Discussionsupporting
confidence: 69%
“…This same pattern, which includes a northern coastal population with an otherwise inland group, has also been described in impala ( Aepyceros melampus ) by Schwab et al (2012) and other South African mammals (Lawes et al, 2007). Cooke (1962), Van Zinderen Bakker (1978) and Scott (2002) suggested that evergreen forest may have stretched from the northern region (NE1/NE2) into KwaZulu-Natal (NC1) before and after the last glacial maxima, 16,000–18,000 years before present.…”
Section: Discussionsupporting
confidence: 69%
“…Both cytb and D-loop detect continental and regional (South Africa) phylogeographic structure respectively [43,44]. The COI phylogenetic tree reflects a similar continental pattern to that of cytb [43].…”
Section: Resultsmentioning
confidence: 99%
“…The Drakensberg Mountains are very old, with an estimated age of 280 million years, which implies that a separation of the vervet populations could have occurred in a time frame ranging from 3 million years ago (during the AGM spread throughout sub-Saharan Africa) to 100,000 years go (during the mass migrations that occurred in the Plio-Pleistocene glacial periods). The Drakensberg Mountains may also have acted as an effective barrier to separate different populations of at least two other species, the common impala ( Aepyceros melampus melampus ) [113] and the chacma baboon ( Papio ursinus ) [114]. We therefore performed relaxed molecular clock analyses to specify TMRCA of the SIVagm samples surrounding the Drakensberg Mountains range to a time-frame spanning 100,000 to 3,000,000 years since the present for the env tree, and in the pol tree we additionally included SIV strains of several species and further calibrated the tree based on isolates from Bioko Island [2].…”
Section: Discussionmentioning
confidence: 99%